Reconocimiento y valoración del activo biológico en la empresa Delai S.A. en el 2018. - Balcazar Añazco, Raquel Elizabeth (Machala : Universidad Técnica de Machala, 2022)
The shrimp industry is one of the main productive activities of the country. In the accounting treatment of this industry, the application of IAS 41 for biological assets is carried out, these must be assessed correctly and according to their importance. Where the International Financial Reporting Standards become the mechanism to consider general and specific policies, with the aim of helping to reduce the difficulties that companies engaged in aquaculture have, such as identifying the sources to which they should resort shrimp producers, and thus be able to provide adequate accounting treatment to each of the accounts that make up the Financial Statements as well as biological assets, including the fair value of the aquaculture product that said biological assets produce, guaranteeing compliance with the regulations and correct decision making of the administration. The objective of the work is to elaborate processes to recognize and value the biological asset in the company Delai S.A. in 2018. For the preparation of this research, the International Accounting Standards have been taken as reference: 41 Agriculture, and the International Financial Reporting Standard 13 Fair Value; In addition, interviews were conducted with external auditors involved in the review of the financial statements of the shrimp sector, in order to identify whether the company has adequate accounting treatment when determining the fair value of the aforementioned assets. It is important that shrimp sector companies can recognize and value assets for the correct decision making as well as the fulfillment of their tax obligations.
La industria del camarón es una de las principales actividades productivas del país. En el tratamiento contable de esta industria se realiza la aplicación de las NIC 41 para los activos biológicos estos deben ser valorados de forma correcta y acorde a su importancia. Donde las Normas Internacionales de Información Financiera, se convierten en el mecanismo para considerar las políticas generales y específicas, con el objetivo de ayudar a disminuir las dificultades que poseen las compañías dedicadas a la actividad acuícola, como el identificar las fuentes a las cuales deben recurrir los productores camaroneros, y así poder brindarles un adecuado tratamiento contable a cada una de las cuentas que integran los Estados Financieros como a los activos biológicos, incluyendo el valor razonable del producto acuícola que dichos activos biológicos producen, garantizando el cumplimiento de las normas y la correcta toma de decisiones de la administración. El objetivo del trabajo es elaborar procesos para reconocer y valorar el activo biológico en la empresa Delai S.A. en el 2018. Para la elaboración de esta investigación se ha tomado como referencia las Normas Internacionales de Contabilidad: 41 Agricultura, y la Norma Internacional de Información Financiera 13 Valor Razonable; además se realizaron entrevistas a directivos y personal del área contable involucrados en la revisión de los estados financieros de la organización, con el fin de identificar que la compañía cuenta con un adecuado tratamiento contable al momento de determinar el valor razonable de los activos antes mencionados. Es importante que las empresas del sector camaronero puedan reconocer y valorar los activos para la correcta toma de decisiones así como el cumplimiento de sus obligaciones tributarias.
Keywords: NIC 41; ACTIVO BIOLÓGICO; VALOR RAZONABLE; ACUICULTURA